STUDI LABORATORIUM: OPTIMASI INJEKSI SURFAKTAN DENGAN METODE INTERMITEN UNTUK MEMPEROLEH PEROLEHAN MINYAK MAKSIMUM DARI RESERVOIR OIL WET - Fauzi Winanda, Dito
About half of the world oil reserves are located in carbonate reservoirs (Roehl and Choquette, 1985), where 65% of the total carbonate reservoirs are oil wet and 12% intermediate wet (Chillingar and Yen, 1985). Oil recoveries in oil wet or mixed wet carbonate reservoirs can be increased by dissolving surfactant to injected water to change the rock wettability from oil wet to more water wet. This laboratory study consists of three main process, making artificial oil wet core, spontaneous imbibition test, and dynamic imbibition test. As we know, carbonate rocks are non-clastic rock which were never made artificially because it was degenerated from other rocks and microorganism in certain pressure and temperature. Because of that, in this study, the author tries to make artificial carbonate core by approaching its wettability characteristic, which commonly is oil wet. From this study, artificial oil wet core can be obtained by mixing chalk, coral, quartz, cement, and water with certain composition. Spontaneous Imbibition test were conducted to choose the best surfactant to be applied in the oil wet reservoir. The surfactant used were S12A* (non-ionic), S13A* (non-ionic), S14A* (anionic), kation 1 dan kation 4. For comparison the test were also done by using the formation water. From the experiment shows that S14A*(anionic) produce the highest oil recovery. Surfactant adsorption to the surface of the rock were able to decrease the interfacial tension making the surface more water wet. Dynamic Imbibition test were conducted by injecting the best surfactant from previous experiment. In this experiment, the author make a simple dynamic imbibition apparatus to support the experiment. The experiment consists of three scenarios based on various open-close injection time and injection rates. This experiment shows that low injection rates tends to increase oil recovery. Besides that, longer closing time tends to increase oil recovery. Management strategies of injection rates and open-close time can be the solution to avoid long closing time but produce optimum oil recovery.